Simultaneous and alternative IgG seroreactivity against Helicobacter pylori antigens VacA, 30 kDa and 50 kDa is a better biomarker approach for the outcome of infection than VacA and 50 kDa alone - Manojlović, Nebojša; Tufegdžić, Ivana; Ristanović, Elizabeta; Bokonjić, Dubravko (Vojnosanitetski pregled, 2022)
Background/Aim. In our previous study, IgG seropositivities against Helicobacter (H) pylori antigens VacA, 50 kDa, 30 kDa, and 26 kDa were highlighted as biomarkers for the specific outcome of infection. We designed and conducted this study in order to investigate whether  synchronous and/or alternative seroreactivity against H. pylori antigens VacA, 50 kDa, 30 kDa and 26 kDa in patients with gastric cancer and peptic ulcers exhibit stronger association than with dyspepsia and vice versa. Methods. In order to determine IgG antibodies to H. pylori antigens, a Western blot test was performed in 123 patients: 31 with gastric cancer, 31 with duodenal ulcer, 31 with gastric ulcer and 30 with functional dyspepsia. We analyzed IgG seroreactivity against four H. pylori antigens (VacA, 50 kDa, 30 kDa, 26 kDa) in their synchronous/alternative combination as well as seroreactivity to synchronous and alternative combinations of H. pylori antigens between a group with functional dyspepsia and others. The analysis of diagnostic characteristics of the best synchronous and alternative seroreactivity combination was done, and tested versus VacA as biomarker for gastric cancer and peptic ulcer, and 50 kDa as a biomarker for dyspepsia. Results. VacA seropositivity or 50 kDa seronegativity (p = 0.015) and VacA seropositivity or 50 kDa and 30 kDa seronegativity (p =0.044) had the better diagnostic characteristics with statistically significantly better fraction correct than VacA seropositivity alone. VacA seronegativity along with50 kDa and 30 kDa seropositivity (p = 0.003), 50 kDa seropositivity (p = 0.01), 30 kDa seropositivity (p = 0.015) and 50 kDa or 30 kDa seropositivity (p = 0.02) had better diagnostic characteristics and significantly better fraction correct than 50 kDa seropositivity alone. Conclusion. Simultaneous and alternative IgG seroreactivity/unreactivity against H. pylori antigens VacA, 50 kDa and 30 kDa have stronger association with the specific infection outcome, considering gastric cancer and peptic ulcer, or dyspepsia, than VacA and 50 kDa IgG seropositivity alone.
Keywords: antigens; biomarkers; duodental ulcer; helicobacter pylori; stomach neoplasms; stomach ulcer